2015
DOI: 10.1097/pec.0000000000000601
|View full text |Cite
|
Sign up to set email alerts
|

Colloids for the Initial Management of Severe Sepsis and Septic Shock in Pediatric Patients

Abstract: The studies analyzed did not find evidence to suggest that the use of colloids is superior to crystalloids. In some studies, the fluid volume needed to achieve initial stabilization was smaller in the group given colloids. Crystalloids are the preferred therapeutic option because of their effectiveness, low cost, and wide availability. Colloids may be the first choice in cases of malaria when the central nervous system is affected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 28 publications
0
11
0
2
Order By: Relevance
“…The findings of this survey indicates a good, at least presumed, compliance of pediatric intensivists in KSA to the SSC guidelines with regards to fluid resuscitation, and initiation of vasopressors and early antibiotic therapy. Although previous studies have not shown a difference in outcomes when using crystalloids or colloid for fluid resuscitation, 13 , 14 most respondents reported using crystalloids as the first choice for fluid resuscitation. Pediatric intensivists mainly use clinical parameters to assess fluid responsiveness as therapeutic end points (vital signs, urine output and skin perfusion), ScvO 2 , and CVP were second choices for assessment.…”
Section: Discussionmentioning
confidence: 81%
“…The findings of this survey indicates a good, at least presumed, compliance of pediatric intensivists in KSA to the SSC guidelines with regards to fluid resuscitation, and initiation of vasopressors and early antibiotic therapy. Although previous studies have not shown a difference in outcomes when using crystalloids or colloid for fluid resuscitation, 13 , 14 most respondents reported using crystalloids as the first choice for fluid resuscitation. Pediatric intensivists mainly use clinical parameters to assess fluid responsiveness as therapeutic end points (vital signs, urine output and skin perfusion), ScvO 2 , and CVP were second choices for assessment.…”
Section: Discussionmentioning
confidence: 81%
“…This is because the use of HA as a volume expander in critically ill patients in septic shock is considered safe (Caraceni et al, 2015). However, when comparing the use of colloids (HA) and crystalloids as volume expander, no superiority was found in relation to the effectiveness of the colloid on the crystalloid, so that the crystalloid is recommended as a first choice solution because its lower cost and lower rate of adverse effects (Medeiros et al, 2015). However, in the case of hepatorenal syndrome, the use of HA is already considered a formal indication (Valerio et al, 2016;Bernardi, Ricci, Zaccherini, 2014).…”
Section: Maldistributive Shockmentioning
confidence: 99%
“…3 Actually, balanced crystalloid solutions are recommended not only in adults but also in pediatric intensive care. [24][25][26][27] The use of crystalloid fluids in neonatology, especially in preterm infants, has to be investigated.…”
Section: Fluid Therapymentioning
confidence: 99%